Thermally induced relaxation of optical absorption and photochromic effect in Bi₁₂SiO₂₀:Cu crystals - Panchenko, T.V.; Strelets, K.Yu. (Functional Materials, 2007)
Spectral kinetics characteristics of photochromic effect and optical destruction of these effect in BSO:Cu crystals have been investigated. It has been shown that both effects are due to the photogeneration and optical destruction of the CuBi²⁺-O and BiSi³⁺ color centers with Cu⁴⁺ ions in Bi³⁺ positions and Bi³⁺ ions in Si⁴⁺. The relaxation parameters of these processes have been shown to depend on temperature.